Factors Determining Seagrass Blue Carbon Across Bioregions and Geomorphologies. Issue 6 (11th June 2021) - Mazarrasa, Inés; Lavery, Paul; Duarte, Carlos M.; Lafratta, Anna; Lovelock, Catherine E.; Macreadie, Peter I.; Samper‐Villarreal, Jimena; Salinas, Cristian; Sanders, Christian J.; Trevathan‐Tackett, Stacey; Young, Mary; Steven, Andy; et al.
Abstract: Seagrass meadows rank among the most significant organic carbon (Corg ) sinks on earth. We examined the variability in seagrass soil Corg stocks and composition across Australia and identified the main drivers of variability, applying a spatially hierarchical approach that incorporates bioregions and geomorphic settings. Top 30 cm soil Corg stocks were similar across bioregions and geomorphic settings (min‐max: 20–26 Mg Corg ha −1 ), but meadows formed by large species (i.e., Amphibolis spp. and Posidonia spp.) showed higher stocks (24–29 Mg Corg ha −1 ) than those formed by smaller species (e.g., Halodule, Halophila, Ruppia, Zostera, Cymodocea, and Syringodium ; 12–21 Mg Corg ha −1 ). In temperate coastal meadows dominated by large species, soil Corg stocks mainly derived from seagrass Corg (72 ± 2%), while allochthonous Corg dominated soil Corg stocks in meadows formed by small species in temperate and tropical estuarine meadows (64 ± 5%). In temperate coastal meadows, soil Corg stocks were enhanced by low hydrodynamic exposure associated with high mud and seagrass Corg contents. In temperate estuarine meadows, soil Corg stocks were enhanced by high contributions of seagrass Corg, low to moderate solar radiation, and low human pressure. In tropical estuarine meadows formed by small species, large soil Corg stocks were mainly associated with low hydrodynamic energy, low rainfall, and high solar radiation. These results showcase that bioregion and geomorphic setting are not necessarily good predictors of soil Corg stocks and that site‐specific estimates based on local environmental factors are needed for Blue Carbon projects and greenhouse gases accounting purposes. Key Points: Australian seagrasses contain higher soil organic carbon stocks than adjacent unvegetated areas due to higher seagrass inputs Seagrass soil carbon stocks are similar over bioregions and geomorphic settings but higher in larger species compared to smaller species Factors determining seagrass soil carbon stocks differ across bioregions and coastal geomorphic settings within bioregions